The Effectiveness of The Jigsaw Cooperative Learning Model in Improving Islamic Religious Education Learning Outcomes - Ziada Hilmi Hanifah; Nurul Kasanah; M.Faizurrizqi Al-Farisi AD (Attanwir : Jurnal Keislaman dan Pendidikan, 2025)
This research examines the effectiveness of the Jigsaw cooperative learning model in improving Islamic Religious Education learning outcomes, focusing on the problems of teacher-centered approaches that lead to low active participation among students at MIN 9 Nganjuk. The research aims to analyze the significance of implementing the Jigsaw cooperative learning model on improving Islamic Religious Education learning outcomes for Asma’ul Husna material. The study employs a quantitative approach with a quasi-experimental one-group pretest-posttest design involving 25 fifth-grade students (13 boys and 12 girls). The research instrument consists of a learning outcome test with 25 items (15 multiple-choice and 10 essay questions) validated through expert judgment and empirical validity testing with a Cronbach's Alpha reliability coefficient of 0.89. Data analysis results show a significant increase in average learning outcomes from 71.6 in the pretest to 92.4 in the posttest with a t-value of -11.43 (p < 0.05). The transformation in learning outcome distribution is evident, with the majority of students initially in the low category (48%) shifting to the very high category (56%) after model implementation. The research conclusion confirms that the Jigsaw cooperative learning model effectively improves Islamic Religious Education learning outcomes through the integration of social constructivism principles, metacognitive skill development, and extrinsic cognitive load reduction that aligns with the Islamic values of ta'awun (mutual assistance) and ukhuwah (brotherhood) in Islamic education.